Wh-filler-gap dependency formation guides reflexive antecedent search - Frazier, Michael; Ackerman, Lauren; Baumann, Peter; Potter, David; Yoshida, Masaya (Frontiers in Psychology, 2015)
Prior studies on online sentence processing have shown that the parser can resolve non-local dependencies rapidly and accurately. This study investigates the interaction between the processing of two such non-local dependencies: wh-filler-gap dependencies (WhFGD) and reflexive-antecedent dependencies. We show that reflexive-antecedent dependency resolution is sensitive to the presence of a WhFGD, and argue that the filler-gap dependency established by WhFGD resolution is selected online as the antecedent of a reflexive dependency. We investigate the processing of constructions like (1), where two NPs might be possible antecedents for the reflexive, namely which cowgirl and Mary. Even though Mary is linearly closer to the reflexive, the only grammatically licit antecedent for the reflexive is the more distant wh-NP, which cowgirl. 1. Which cowgirl did Mary expect to have injured herself due to negligence? Four eye-tracking text-reading experiments were conducted on examples like (1), differing in whether the embedded clause was non-finite (1 and 3) or finite (2 and 4), and in whether the tail of the wh-dependency intervened between the reflexive and its closest overt antecedent (1 and 2) or the wh-dependency was associated with a position earlier in the sentence (3 and 4). The results of Experiments 1 and 2 indicate the parser accesses the result of WhFGD formation during reflexive antecedent search. The resolution of a wh-dependency alters the representation that reflexive antecedent search operates over, allowing the grammatical but linearly distant antecedent to be accessed rapidly. In the absence of a long-distance WhFGD (Exp. 3 and 4), wh-NPs were not found to impact reading times of the reflexive, indicating that the parser's ability to select distant wh-NPs as reflexive antecedents crucially involves syntactic structure.